Preparation method of chlorinated polyvinyl chloride modified material

Through chemical grafting and physical blending technology, combined with nanomontmorillonite and long-chain fatty acid ester grafted chlorinated paraffin, the thermal stability and toughness of chlorinated polyvinyl chloride materials have been modified, which solves the problems of difficult processing and forming and insufficient impact resistance, significantly improves the performance of the material and expands its application range.

CN119552468AInactive Publication Date: 2025-03-04ZHEJIANG ART PIPE IND (WUHAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411874986.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While improving performance, chlorinated polyvinyl chloride materials have problems such as difficulty in processing and forming, poor surface finish, insufficient impact resistance and low thermal stability, which limits its application prospects.

Method used

Block isooctyl acrylate is synthesized by chemical grafting reaction and modified chlorinated polyvinyl chloride of dodecenyl succinic anhydride, and crosslinked styrene and acrylonitrile fibers through physical blending to form a network-like crosslinked block chlorinated polyvinyl chloride, combining nanomontmorillonite and long-chain fatty acid ester grafted chlorinated paraffin, synergistically improving the thermal stability and toughness of the material.

Benefits of technology

It significantly improves the thermal stability, strength and toughness of chlorinated polyvinyl chloride, reduces melt viscosity, improves processing performance and impact resistance, and makes the material more suitable for heat-resistant and impact-resistant polymer material products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552468A_ABST
    Figure CN119552468A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a preparation method of a chlorinated polyvinyl chloride modified material, which is prepared by chlorination of polyvinyl chloride by a chemical grafting method, block of 2-ethylhexyl acrylate and grafting of dodecenyl succinic anhydride. Net-shaped cross-linked block chlorinated polyvinyl chloride prepared by cross-linking acrylonitrile fibers and poly-alpha-methyl styrene through a physical blending method is used, and long-chain fatty acid ester containing active proton pellet groups is grafted on chlorinated paraffin to serve as a main stabilizer. The molecular structure of the obtained chlorinated polyvinyl chloride modified material is more excellent, and the strength, the thermal stability and the heat resistance of the chlorinated polyvinyl chloride modified material are greatly improved; the impact-resistant chlorinated polyvinyl chloride improves the self-defect of poor impact resistance of chlorinated polyvinyl chloride, obviously improves the plasticity, widens the application range, and is especially suitable for preparation of heat-resistant and impact-resistant high polymer material products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a chlorinated polyvinyl chloride modified material. Background Art

[0002] Chlorinated polyvinyl chloride is made by chlorination modification of polyvinyl chloride. After chlorination modification, the chlorine content of the material is increased from 56.7% to 63%-68%, thereby increasing the molecular bond polarity, intermolecular force, and chemical stability of the material, and greatly improving the mechanical properties, chemical corrosion resistance, and flame retardant properties of the material. However, with the increase of chlorine content, while some properties are improved, some properties are also insufficient: due to the high melt viscosity and difficulty in processing and molding of chlorinated polyvinyl chloride materials, the surface finish of its products is poor and the impact resistance is poor. Although the heat resistance of the material has been improved, the thermal stability is not high, the processing performance is not good, the melting temperature is close to its decomposition temperature, and it is easy to overheat and decompose. These defects greatly limit the application prospects of chlorinated polyvinyl chloride resins.

[0003] At present, both domestic and foreign researchers are focusing on large-scale modification research on chlorinated polyvinyl chloride in order to improve its defects.

[0004] The Chinese patent with publication number CN115584096B discloses a chlorinated polyvinyl chloride composition and its preparation method and application. The chlorinated polyvinyl chloride composition of the invention is prepared with CPVC resin, main stabilizer, auxiliary stabilizer, lubricant, impact modifier, antioxidant, colorant and pigment as raw materials. On the basis of using the main stabilizer, a basic first metal salt with a layered structure, a second metal salt and a hydroxylamine compound with a strong oxidizing effect are further added as auxiliary stabilizers. The synergistic effect between the three is utilized to make the chlorinated polyvinyl chloride composition have a longer stability time and better stability performance, which can ensure that the chlorinated polyvinyl chloride pipe obtained has good heat resistance and thermal stability. Although the method improves the heat resistance and thermal stability of the chlorinated polyvinyl chloride composition, the overall strength and overall strength and softening point are in a downward trend.

[0005] Publication number CN113683851B discloses a method for improving the processing performance of chlorinated polyvinyl chloride resin. The invention uses ultra-high molecular weight chlorinated polyethylene as a processing modifier for chlorinated polyvinyl chloride resin, so that the obtained mixture has good demoulding performance and improves its toughness without affecting the Vicat softening point. Although this method improves the processing performance and toughness of chlorinated polyvinyl chloride resin, as the chlorine content of chlorinated polyvinyl chloride increases, its brittleness increases, the impact strength of the resulting product becomes lower, and it is easy to show tiny cracks during the deformation process. And as the chlorine content of chlorinated polyvinyl chloride increases, while some of its performance is improved, it also shows deficiencies in some aspects, mainly its narrow processing temperature range; high melt viscosity, difficult processing and molding;

[0006] Therefore, since the industrialization of chlorinated polyvinyl chloride, people have been looking for an effective way. How to make chlorinated polyvinyl chloride maintain its high strength, high plasticity and high heat resistance while improving its impact properties and reducing its melt viscosity is the difficulty of current research. Summary of the invention

[0007] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing a chlorinated polyvinyl chloride modified material to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0008] The object of the present invention is achieved by the following technical scheme: a chlorinated polyvinyl chloride modified material, which is prepared from the following raw materials in parts by mass: 100-120 parts of chlorinated polyvinyl chloride with a network cross-linked block; 5-8 parts of a main stabilizer; 1-2 parts of an auxiliary stabilizer; 2.0-4.0 parts of a composite lubricant; 0.3-0.5 parts of an antioxidant; and 1.5-2.5 parts of a colorant;

[0009] The network cross-linked block chlorinated polyvinyl chloride is prepared by cross-linking modified chlorinated polyvinyl chloride and poly-α-methylstyrene and acrylonitrile fiber, and the modified chlorinated polyvinyl chloride is prepared by chlorinating polyvinyl chloride, blocking isooctyl acrylate and grafting dodecenyl succinic anhydride;

[0010] First, the modified chlorinated polyvinyl chloride is prepared, specifically:

[0011] S001, add polyvinyl chloride powder, talcum powder and deionized water to a reactor, stir and mix to obtain a uniform suspension, introduce nitrogen to remove air in the reactor, use a vacuum pump to evacuate the gas in the reactor to negative pressure, slowly raise the temperature to 85-88°C, then drop in initiator dibenzoyl peroxide, introduce chlorine, and allow polyvinyl chloride and chlorine to react under a certain pressure. After reacting for 150-200 minutes, add dodecenyl succinic anhydride and isooctyl acrylate, stir evenly, slowly raise the temperature to 90-95°C, introduce chlorine for the second time, and continue to react for 5-7 hours to obtain a crude product;

[0012] Among them, chlorine is initially passed through at a rate of 1.8-2.1 kg / min, and the pressure in the kettle is controlled at 0.5-0.6 MPa; the second chlorine chlorination is carried out at a rate of 3.8-4.2 kg / min, the heating rate is controlled at 0.07-0.12°C / min, the temperature is raised to 90-95°C, and the pressure in the kettle is controlled at 0.6-1.0 MPa.

[0013] S002, after the reaction is completed, stop heating, and when the reaction temperature drops to room temperature, use nitrogen to blow out the remaining chlorine to the alkali solution tank for absorption. Take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and use pH test paper to measure the pH value of the washing liquid. When the washing liquid is neutral, filter and pour tetrahydrofuran to completely dissolve it, then add methanol to fully precipitate it, and then filter it. Obtain a graft copolymer of block-polymerized isooctyl acrylate grafted with dodecenyl succinic anhydride on the side chain to modify chlorinated polyvinyl chloride, and finally place it in a vacuum drying oven and dry it at 60±2℃ to constant weight.

[0014] Among them, 100-120 parts of polyvinyl chloride powder, 2-4 parts of talc, 1-2 parts of dibenzoyl peroxide, 150-250 parts of deionized water; the mass ratio of dodecenyl succinic anhydride, isooctyl acrylate and polyvinyl chloride powder is 6-8:20-30:100-120;

[0015] The double bonds and anhydride groups in dodecenylsuccinic anhydride enable it to participate in many chemical reactions. At the same time, due to the strong polarity and high subsequent reactivity of the anhydride group, it can be used to modify the chlorinated polyvinyl chloride body. This method uses the free radicals (Cl·) generated by the thermal decomposition of chlorine as an initiator to capture hydrogen on the backbone polymer. While the polymer free radicals undergo chlorination according to the free radical mechanism, they can also undergo graft copolymerization with monomers in the system that can be polymerized according to the free radical mechanism, thereby obtaining a graft copolymer of the chlorinated polymer. The characteristic of this process is that modified chlorinated polyvinyl chloride is obtained during the preparation of chlorinated polyvinyl chloride, and chlorine has high activity. There are many active points on the polyvinyl chloride backbone polymer that can be activated by chlorine, which can form a graft copolymer with multiple branching points and has a high grafting rate, and the modification effect is obvious.

[0016] Dodecenyl succinic anhydride is grafted onto the main chain of chlorinated polyvinyl chloride to reduce the Cl substituents on the main chain; in addition, it is possible that it can occupy the more active allylic position as a substituent, that is, the substituent on the allylic position is dodecenyl succinic anhydride instead of Cl. These will greatly inhibit the removal of HCl and block the formation of a conjugated structure of the molecular chain during the dehydrochlorination process.

[0017] The modified chlorinated polyvinyl chloride obtained after graft copolymerization has improved thermal stability and greatly improved mechanical properties. However, its brittleness is also greatly increased due to the chlorine content. How to increase its toughness and plasticity on the basis of improving thermal stability and mechanical properties is a further problem that needs to be solved.

[0018] Furthermore, the modified chlorinated polyvinyl chloride is physically blended with poly-α-methylstyrene and acrylonitrile fiber to obtain a network cross-linked block chlorinated polyvinyl chloride, specifically:

[0019] S101, adding modified chlorinated polyvinyl chloride, poly-α-methylstyrene and acrylonitrile fiber into a reaction kettle, and under nitrogen protection, heating to 130-180° C., stirring at a speed of 500 rpm, so that poly-α-methylstyrene and acrylonitrile fiber are uniformly dispersed in the modified chlorinated polyvinyl chloride, and continuing the reaction for 60-80 minutes to obtain a network cross-linked block chlorinated polyvinyl chloride; wherein the mass ratio of acrylonitrile fiber, poly-α-methylstyrene and modified chlorinated polyvinyl chloride is 2-4:8-15:100;

[0020] First, dodecenyl succinic anhydride was grafted through chemical modification, and styrene and acrylonitrile were cross-linked through physical blending to improve the melt fluidity of chlorinated polyvinyl chloride. From the morphological structure point of view, styrene and acrylonitrile chain segments are distributed in the inner layer, while the chlorinated polyvinyl chloride grafted with dodecenyl succinic anhydride is cross-linked in the outer layer. The two have good compatibility, which makes the surface of the trial product smooth, with good toughness and high strength.

[0021] Since chlorinated polyvinyl chloride is easy to degrade during processing, the molding temperature must be above 170-200°C to process chlorinated polyvinyl chloride into useful products. Therefore, stabilizers must be added for stabilization treatment. The main stabilizer is modified from chlorinated paraffin, long-chain fatty acid ester and nano-montmorillonite, specifically:

[0022] S201, selecting nano calcium-based montmorillonite with a diameter of 50 to 80 nm, adding the nano calcium-based montmorillonite to deionized water, adding dilute hydrochloric acid and stirring evenly, so that the nano calcium-based montmorillonite is fully dispersed in the dilute hydrochloric acid solution, heating to 60° C., adding octadecyltrimethylammonium chloride, stirring well, reacting for 1 to 2 hours, and obtaining a suspension of nano calcium-based montmorillonite;

[0023] S202, adjusting the pH value of the suspension of nano calcium-based montmorillonite to 3.2-3.5 with hydrochloric acid, adding glutamic acid, stirring thoroughly, reacting for 2 hours, taking out the reaction solution and centrifuging at a speed of 3000 rpm, washing with deionized water 2-3 times to remove the hydrochloric acid, centrifuging again, taking out the solid mixture at the bottom, drying and grinding at 60° C. to obtain nano calcium-based montmorillonite with a positive charge on the outer layer, recorded as active proton particles; glycerol and octadecyl dimethyl tertiary amine are mixed in a mass ratio of 1:1; the mass ratio of the octadecyl dimethyl tertiary amine to the nano calcium-based montmorillonite is 1:4; the mass ratio of glutamic acid to the nano calcium-based montmorillonite is 1:1;

[0024] S203, add glycerol and chlorinated paraffin to the reactor, stir evenly, add thiosalicylic acid and potassium carbonate, and heat to 50-60°C for 5-8 hours under nitrogen protection. After the reaction is completed, extract with ethanol and vacuum dry at 100°C for 2 hours. Pour the obtained light yellow liquid into tetrahydrofuran, adjust the pH value to 4 with hydrochloric acid, then pour into ethanol for extraction, vacuum dry at 80°C for 2 hours to obtain a light yellow liquid; the mass ratio of thiosalicylic acid, potassium carbonate and chlorinated paraffin is 1:1:2;

[0025] S204, adding chloroform, long-chain fatty acid ester and N,N-dimethylformamide to the light yellow liquid, stirring and reacting at 60-70° C. for 4-6 hours, extracting with ethanol, and vacuum drying at 80° C. for 2 hours to obtain a yellow liquid in which the long-chain fatty acid ester is grafted onto the chlorinated paraffin; the mass ratio of the long-chain fatty acid ester to the chlorinated paraffin is 1:1;

[0026] S205, adding active proton particles into the yellow liquid, stirring at high speed to disperse evenly, to obtain a main stabilizer, the mass ratio of active proton particles to long-chain fatty acid ester grafted chlorinated paraffin is 1:8-10.

[0027] The CPVC molecular chain includes allyl chloride, active hydrogen atoms and chlorine atoms, double bonds and oxygen-containing groups. Even if it is grafted with dodecenyl succinic anhydride, the removal of HCl is greatly inhibited, blocking the formation of a conjugated structure in the molecular chain during the dehydrochlorination process. However, when the temperature is high enough, CPVC will decompose when heated, and HCl will be removed first. The escaped HCl will further promote the removal of HCl in the CPVC molecular chain. In particular, this extensive self-catalytic dehydrochlorination reaction will intensify the reaction if it is exposed to high temperature conditions during processing, resulting in the formation of conjugated olefins very early in the processing process, which leads to a rapid decline in physical and mechanical properties. When the main stabilizer of long-chain fatty acid ester grafted chlorinated paraffin containing active proton particles is added to the reaction system, the nano-montmorillonite and the chlorinated paraffin grafted with long-chain esters work synergistically to absorb the hydrogen chloride produced by the decomposition of chlorinated polyvinyl chloride, and can also react with unstable chlorine atoms to prevent the formation of colored large conjugated bonds, or carry out molecular addition reactions of conjugated double bonds to stabilize the molecular structure. At the same time, it can also capture free radicals produced by the decomposition of large molecules, decompose the thermal decomposition intermediate-hydroperoxide, and further prevent the degradation of the polymer. At the same time, the active proton particles are composed of two silica tetrahedrons and one alumina hexahedron. The microspheres with lamellar structures have holes and channels of various sizes, and the surface contains NH 4+ , its inner layer contains atoms such as Ca, Al and Si, which can effectively absorb hydrogen chloride produced by the degradation of chlorinated polyvinyl chloride, and prevent the presence of hydrogen chloride from causing further degradation of the resin. From the perspective of compatibility, ester plasticizers, especially long-chain fatty acid esters, have a structure composed of two parts, namely, non-polar alkyl segments and polar ester segments. The non-polar part has a certain repulsive force with the polar molecular chain of chlorinated polyvinyl chloride, which allows the macromolecular chain to slowly aggregate and form a small-sized colloid cluster. The liquid-solid interface formed by the non-polar part between the colloid clusters reduces the friction in the system and plays an internal lubricating role; while the polar part produces an entanglement shielding effect by untangling the chlorinated polyvinyl chloride molecular chain in the colloid cluster, providing sufficient free volume for the transformation of the molecular chain conformation, and gradually stabilizes the increased free volume to form a three-dimensional network cross-linked structure. The polar part of the ester group and C-Cl group also contains an alkyl chain as a non-polar group, which can not only play an internal lubricating role, but also force the macromolecular chain to bundle and disentangle, achieving a better plasticizing efficiency, while greatly reducing the viscosity of the plasticized paste. Therefore, the chlorinated polyvinyl chloride modified material prepared by the reaction system completely prevents the stability problem caused by the escape of small molecular substances, not only significantly improves the thermal stability and mechanical properties, but also increases its processability.

[0028] The auxiliary stabilizer is an organic tin stabilizer, which is any one of methyl tin mercaptan and octyl tin mercaptan;

[0029] The composite lubricant is prepared by mixing oxidized polyethylene wax and ethylene bisstearamide in a mass ratio of 1:1-2.

[0030] The antioxidant includes at least one of p-diisooctyldiphenylamine and 2,6-tert-butyl-4-methylphenol; and the colorant is titanium dioxide.

[0031] Finally, the preparation method of the chlorinated polyvinyl chloride modified material is specifically as follows:

[0032] S301, weigh the chlorinated polyvinyl chloride of the network cross-linked block, the main stabilizer, the auxiliary stabilizer, the composite lubricant, the antioxidant and the colorant according to the formula for use.

[0033] S302, first pour the network cross-linked block chlorinated polyvinyl chloride into a high-speed mixer, mix at a speed of 800-1000r / min until the temperature reaches 75°C-85°C, then pour the main heat stabilizer into the high-speed mixer and continue to mix until the temperature reaches 88°C-92°C, then pour the auxiliary stabilizer, composite lubricant, antioxidant, and colorant into the high-speed mixer and continue to mix until the temperature reaches 110°C-130°C, discharge the material, and send the mixed material into a cooling agitator to cool it to 30°C-40°C, so as to obtain the chlorinated polyvinyl chloride modified material.

[0034] The invention synthesizes the modified chlorinated polyvinyl chloride functionalized with anhydride groups of block acrylate and grafted with dodecenyl succinic anhydride by chemical grafting reaction, and crosslinks styrene and acrylonitrile by physical blending to obtain network crosslinked block chlorinated polyvinyl chloride, which greatly improves the strength and softening point of chlorinated polyvinyl chloride while improving the thermal stability and toughness. The chlorinated polyvinyl chloride synthesized at last has the characteristics of short branching and multiple branching points in its molecular structure. The product contains chlorine not only on the main chain of the molecule but also on the side chain. The strong polar groups (anhydride groups) introduced on the macromolecular chain increase the polarity and rigidity of the molecular chain and enhance the interaction force of the molecular chain, thereby significantly improving the strength of the material. In addition, because the double bond structure and partial chlorine structure in the molecular chain are reduced, and the long-chain fatty acid ester grafted chlorinated paraffin containing active proton particles is used, the dechlorination reaction of the double bond and partial chlorine structure on the molecular chain during the polymer thermoforming process is completely suppressed, making the molecular structure of the material more superior, and its strength, toughness, thermal stability and heat resistance are greatly improved. The inherent defect of chlorinated polyvinyl chloride, which is poor in impact resistance, is improved, so that the plasticity is also significantly improved, and its scope of use is expanded, and it is particularly suitable for the preparation of heat-resistant and impact-resistant polymer material products.

[0035] In the prior art, the dechlorination reaction of double bonds and partial chlorine structures in the polymer thermoforming process cannot be effectively suppressed in the synthesis reaction of chlorinated polyvinyl chloride, and the HCl autocatalytic substance generated in the reaction cannot be captured, so that the prepared chlorinated polyvinyl chloride material has poor thermal stability and greatly reduced mechanical properties. Compared with the prior art, the beneficial effects of the invention are:

[0036] 1) The present invention provides a method for preparing a modified chlorinated polyvinyl chloride material. The modified chlorinated polyvinyl chloride functionalized with block isooctyl acrylate and grafted with dodecenyl succinic anhydride is synthesized by chemical grafting reaction, and styrene and acrylonitrile fibers are cross-linked by physical blending to obtain a network-crosslinked block chlorinated polyvinyl chloride. The synergistic effect of the two makes the chlorinated polyvinyl chloride mixture have excellent thermal stability, and the Vicat softening temperature reaches 120-130°C, which greatly reduces the difficulty of plasticizing the chlorinated polyvinyl chloride. The chlorinated polyvinyl chloride synthesized at last has the characteristics of short branching and multiple branching points in its molecular structure; the product contains chlorine not only on the main chain of the molecule but also on the side chain; the strong polar groups (anhydride groups) introduced on the macromolecular chain increase the polarity and rigidity of the molecular chain and enhance the interaction force of the molecular chain, thereby significantly improving the strength of the material; and because the double bond structure and partial chlorine structure in the molecular chain are reduced, and the long-chain fatty acid ester grafted chlorinated paraffin containing active proton particles is used, the dechlorination reaction of the double bond and partial chlorine structure on the molecular chain during the polymer thermoforming process is completely suppressed, making the molecular structure of the material more superior, and its strength, thermal stability and heat resistance are greatly improved; the inherent defect of chlorinated polyvinyl chloride, which is poor in impact resistance, is improved, so that the plasticity is also significantly improved, and its scope of use is expanded, and it is particularly suitable for the preparation of heat-resistant and impact-resistant polymer products.

[0037] 2) The present invention also provides a method for preparing a stabilizer. When the long-chain fatty acid ester containing active proton particles is grafted onto chlorinated paraffin as the main stabilizer, the nano-montmorillonite and the chlorinated paraffin grafted with the long-chain ester act synergistically to absorb the hydrogen chloride generated by the decomposition of chlorinated polyvinyl chloride, and can also react with unstable chlorine atoms to prevent the formation of colored large conjugated bonds, or to carry out molecular addition reactions of conjugated double bonds, stabilize the molecular structure, and can also capture free radicals generated by the decomposition of macromolecules, decompose the thermal decomposition intermediate-hydroperoxide, and further prevent the degradation of the polymer. At the same time, the long-chain ester and chlorinated paraffin also have a lubricating effect. The high specific surface area of ​​the nano-montmorillonite is used to improve the dispersibility and surface adhesion of the lubricant, so that the effect of the lubricant is improved, the melt viscosity is reduced, and the plasticization is uniform, thereby improving the problem that the melt viscosity of the chlorinated polyvinyl chloride material is large and the molding process is difficult.

[0038] 3) The organic combination of chemical grafting and physical blending, as well as the main stabilizer of long-chain fatty acid ester grafted with chlorinated paraffin containing active proton particles, effectively improves the heat resistance of chlorinated polyvinyl chloride modified materials, expands the melting temperature and thermal decomposition temperature range, and thus the adjustable range of processing temperature of chlorinated polyvinyl chloride modified materials becomes wider, improves processing fluidity, and at the same time improves the toughness of chlorinated polyvinyl chloride mixtures. It can be stable at 200°C for 120 minutes, which greatly reduces the difficulty of plasticizing chlorinated polyvinyl chloride. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 , stability time state diagram of chlorinated polyvinyl chloride modified materials at various temperature points. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0041] Example 1

[0042] A method for preparing a chlorinated polyvinyl chloride modified material, first preparing modified chlorinated polyvinyl chloride, specifically:

[0043] In a reactor, 100 parts of polyvinyl chloride powder, 2 parts of talcum powder and 200 parts of deionized water are added, stirred and mixed to obtain a uniformly mixed suspension, nitrogen is introduced to remove the air in the reactor, the gas in the reactor is evacuated using a vacuum pump to a negative pressure of 0.5 MPa, the temperature is slowly raised to 86°C, and then 1 part of dibenzoyl peroxide as an initiator is added dropwise, chlorine is introduced at a rate of 2.1 kg / min to react polyvinyl chloride with chlorine, after reacting for 150 minutes, 8 parts of dodecenyl succinic anhydride and 20 parts of isooctyl acrylate are added, the temperature is raised to 92°C, the gas in the reactor reaches a negative pressure of 0.8 MPa, and chlorine is introduced at a rate of 3.8 kg / min for the second time to continue the reaction for 5 hours; a crude product is obtained;

[0044] Stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen to the alkali solution tank for absorption, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; obtain the graft copolymer of block polymerized isooctyl acrylate grafted with dodecenyl succinic anhydride on the side chain to modify chlorinated polyvinyl chloride, finally place it in a vacuum drying oven and dry it at 60°C to constant weight.

[0045] Furthermore, the modified chlorinated polyvinyl chloride is physically blended with poly-α-methylstyrene and acrylonitrile fiber to obtain a network cross-linked block chlorinated polyvinyl chloride, and the specific preparation method is as follows:

[0046] 100 parts of modified chlorinated polyvinyl chloride, 8 parts of poly-α-methylstyrene and 4 parts of acrylonitrile fiber were added into a reactor. Under nitrogen protection, the temperature was raised to 150°C and the stirring speed was 500 rpm to uniformly disperse the poly-α-methylstyrene and acrylonitrile fiber in the modified chlorinated polyvinyl chloride. The reaction was continued for 80 minutes to obtain a network cross-linked block chlorinated polyvinyl chloride.

[0047] The main stabilizer modified by chlorinated paraffin, long-chain fatty acid ester and nano-montmorillonite is prepared, specifically:

[0048] Select 20 parts of nano calcium-based montmorillonite with a diameter of 50 to 80 nm, add the nano calcium-based montmorillonite to deionized water, add dilute hydrochloric acid and stir evenly, so that the nano calcium-based montmorillonite is fully dispersed in the dilute hydrochloric acid solution, heat to 60°C, add 5 parts of glycerol and 5 parts of octadecyl dimethyl tertiary amine mixed solution, stir well, react for 2 hours, and obtain a suspension of nano calcium-based montmorillonite. Use hydrochloric acid to adjust the pH value of the suspension to 3.3, then add 20 parts of glutamic acid, stir well, react for 2 hours, take out the reaction solution and centrifuge at a speed of 3000 rpm, wash it with deionized water 3 times to remove the hydrochloric acid, centrifuge again, take out the solid mixture at the bottom, dry and grind it at 60°C, and obtain a nano calcium-based montmorillonite with a positive charge on the outer layer, that is, an active proton particle group;

[0049] Add 50 parts of glycerol and 20 parts of chlorinated paraffin into a reaction kettle, stir evenly, then add 10 parts of thiosalicylic acid and 10 parts of potassium carbonate, and heat to 60°C for reaction for 8 hours under nitrogen protection; after the reaction is completed, extract with ethanol and vacuum dry at 100°C for 2 hours; pour the obtained light yellow liquid into tetrahydrofuran, adjust the pH value to 4 with hydrochloric acid, then pour into ethanol for extraction, and vacuum dry at 80°C for 2 hours to obtain a light yellow liquid;

[0050] 200 parts of chloroform, 20 parts of long-chain fatty acid ester and 0.05 parts of N,N-dimethylformamide were added to 20 parts of light yellow liquid, and stirred at 70°C for 5 hours, and then extracted with ethanol and vacuum dried at 80°C for 2 hours to obtain a yellow liquid of long-chain fatty acid ester grafted chlorinated paraffin;

[0051] Add 5 parts of active proton particles into 40 parts of yellow liquid, stir at high speed to disperse evenly, and obtain the main stabilizer.

[0052] Finally, the preparation method of the chlorinated polyvinyl chloride modified material is specifically as follows:

[0053] First, pour 100 parts of network cross-linked block chlorinated polyvinyl chloride into a high-speed mixer and mix at a speed of 1000r / min until the temperature reaches 85°C, then pour 8 parts of the main heat stabilizer into the high-speed mixer and continue to mix until the temperature reaches 88°C, then pour 1 part of methyl tin mercaptan, 1 part of oxidized polyethylene wax and 2 parts of ethylene bisstearamide, 0.3 parts of diisooctyl diphenylamine, and 1.5 parts of colorant into the high-speed mixer and continue to mix until the temperature reaches 130°C, discharge the material, and send the mixture into a cooling agitator to cool to 40°C to obtain a chlorinated polyvinyl chloride modified material.

[0054] Example 2

[0055] A method for preparing a chlorinated polyvinyl chloride modified material, first preparing modified chlorinated polyvinyl chloride, specifically:

[0056] In a reactor, 120 parts of polyvinyl chloride powder, 4 parts of talcum powder and 200 parts of deionized water were added, stirred and mixed to obtain a uniformly mixed suspension, nitrogen was introduced to remove the air in the reactor, and the gas in the reactor was evacuated using a vacuum pump to a negative pressure of 0.5 MPa, and the temperature was slowly raised to 85°C, and then 2 parts of initiator dibenzoyl peroxide were added dropwise, and chlorine was introduced at a rate of 1.8 kg / min to react polyvinyl chloride and chlorine. After reacting for 150 minutes, 6 parts of dodecenyl succinic anhydride and 30 parts of isooctyl acrylate were added, the temperature was raised to 93°C, the gas in the reactor was at a negative pressure of 1.0 MPa, and chlorine was introduced at a rate of 3.9 kg / min for the second time to continue the reaction for 7 hours; a crude product was obtained;

[0057] Stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen to the alkali solution tank for absorption, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; obtain the graft copolymer of block polymerized isooctyl acrylate grafted with dodecenyl succinic anhydride on the side chain to modify chlorinated polyvinyl chloride, finally place it in a vacuum drying oven and dry it at 60°C to constant weight.

[0058] Furthermore, the modified chlorinated polyvinyl chloride is physically blended with poly-α-methylstyrene and acrylonitrile fiber to obtain a network cross-linked block chlorinated polyvinyl chloride, and the specific preparation method is as follows:

[0059] 100 parts of modified chlorinated polyvinyl chloride, 15 parts of poly-α-methylstyrene and 2 parts of acrylonitrile fiber were added into a reactor. Under nitrogen protection, the temperature was raised to 120°C and the stirring speed was 500 rpm to uniformly disperse the poly-α-methylstyrene and acrylonitrile fiber in the modified chlorinated polyvinyl chloride. The reaction was continued for 60 minutes to obtain a network cross-linked block chlorinated polyvinyl chloride.

[0060] The main stabilizer modified by chlorinated paraffin, long-chain fatty acid ester and nano-montmorillonite is prepared, specifically:

[0061] Select 20 parts of nano calcium-based montmorillonite with a diameter of 50 to 80 nm, add the nano calcium-based montmorillonite to deionized water, add dilute hydrochloric acid and stir evenly, so that the nano calcium-based montmorillonite is fully dispersed in the dilute hydrochloric acid solution, heat to 60°C, add 5 parts of glycerol and 5 parts of octadecyl dimethyl tertiary amine mixed solution, stir well, react for 2 hours, and obtain a suspension of nano calcium-based montmorillonite. Use hydrochloric acid to adjust the pH value of the suspension to 3.5, then add 20 parts of glutamic acid, stir well, react for 2 hours, take out the reaction solution and centrifuge at a speed of 3000 rpm, wash it with deionized water 3 times to remove the hydrochloric acid, centrifuge again, take out the solid mixture at the bottom, dry and grind it at 60°C, and obtain a nano calcium-based montmorillonite with a positive charge on the outer layer, that is, an active proton particle group;

[0062] Add 50 parts of glycerol and 20 parts of chlorinated paraffin into a reaction kettle, stir evenly, then add 10 parts of thiosalicylic acid and 10 parts of potassium carbonate, and heat to 60°C for reaction for 6 hours under nitrogen protection; after the reaction is completed, extract with ethanol and vacuum dry at 100°C for 2 hours; pour the obtained light yellow liquid into tetrahydrofuran, adjust the pH value to 4 with hydrochloric acid, then pour into ethanol for extraction, and vacuum dry at 80°C for 2 hours to obtain a light yellow liquid;

[0063] 200 parts of chloroform, 20 parts of long-chain fatty acid ester and 0.05 parts of N,N-dimethylformamide were added to 20 parts of light yellow liquid, and stirred at 70°C for 6 hours, and then extracted with ethanol and vacuum dried at 80°C for 2 hours to obtain a yellow liquid of long-chain fatty acid ester grafted chlorinated paraffin;

[0064] Add 4 parts of active proton particles into 40 parts of yellow liquid, stir at high speed to disperse evenly, and obtain the main stabilizer.

[0065] Finally, the preparation method of the chlorinated polyvinyl chloride modified material is specifically as follows:

[0066] First, pour 120 parts of network cross-linked block chlorinated polyvinyl chloride into a high-speed mixer, mix at a speed of 1000r / min until the temperature reaches 80°C, then pour 8 parts of a main heat stabilizer into the high-speed mixer and continue to mix until the temperature reaches 90°C, then pour 2 parts of methyl tin mercaptide, 1 part of oxidized polyethylene wax and 2 parts of ethylene bisstearamide, 0.4 parts of 2,6-tert-butyl-4-methylphenol, and 2.0 parts of a colorant into the high-speed mixer and continue to mix until the temperature reaches 120°C, discharge the material, and send the mixture into a cooling agitator to cool to 30°C to obtain a chlorinated polyvinyl chloride modified material.

[0067] Example 3

[0068] A method for preparing a chlorinated polyvinyl chloride modified material, first preparing modified chlorinated polyvinyl chloride, specifically:

[0069] In a reactor, 110 parts of polyvinyl chloride powder, 3 parts of talcum powder and 250 parts of deionized water were added, stirred and mixed to obtain a uniformly mixed suspension, nitrogen was introduced to remove the air in the reactor, and the gas in the reactor was evacuated using a vacuum pump to a negative pressure of 0.5 MPa, and the temperature was slowly raised to 87°C, and then 1.5 parts of initiator dibenzoyl peroxide were added dropwise, and chlorine was introduced at a rate of 2.1 kg / min to react polyvinyl chloride and chlorine. After reacting for 150 minutes, 7 parts of dodecenyl succinic anhydride and 25 parts of isooctyl acrylate were added, the temperature was raised to 93°C, the gas in the reactor was at a negative pressure of 1.0 MPa, and chlorine was introduced at a rate of 4.1 kg / min for the second time to continue the reaction for 7 hours; a crude product was obtained;

[0070] Stop heating, lower the reaction temperature to room temperature, blow out the remaining chlorine with nitrogen to the alkali solution tank for absorption, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; obtain the graft copolymer of block polymerized isooctyl acrylate grafted with dodecenyl succinic anhydride on the side chain to modify chlorinated polyvinyl chloride, finally place it in a vacuum drying oven and dry it at 60°C to constant weight.

[0071] Furthermore, the modified chlorinated polyvinyl chloride is physically blended with poly-α-methylstyrene and acrylonitrile fiber to obtain a network cross-linked block chlorinated polyvinyl chloride, and the specific preparation method is as follows:

[0072] 100 parts of modified chlorinated polyvinyl chloride, 12 parts of poly-α-methylstyrene and 3 parts of acrylonitrile fiber were added to the reactor, and the temperature was raised to 140°C under nitrogen protection, and the stirring speed was 500 rpm, so that the poly-α-methylstyrene and acrylonitrile fiber were evenly dispersed in the modified chlorinated polyvinyl chloride, and the reaction was continued for 80 minutes to obtain a network cross-linked block chlorinated polyvinyl chloride. The main stabilizer modified by chlorinated paraffin, long-chain fatty acid ester and nano-montmorillonite was prepared, specifically:

[0073] Select 20 parts of nano calcium-based montmorillonite with a diameter of 50 to 80 nm, add the nano calcium-based montmorillonite to deionized water, add dilute hydrochloric acid and stir evenly, so that the nano calcium-based montmorillonite is fully dispersed in the dilute hydrochloric acid solution, heat to 60°C, add 5 parts of glycerol and 5 parts of octadecyl dimethyl tertiary amine mixed solution, stir well, react for 2 hours, and obtain a suspension of nano calcium-based montmorillonite. Use hydrochloric acid to adjust the pH value of the suspension to 3.2, then add 20 parts of glutamic acid, stir well, react for 2 hours, take out the reaction solution and centrifuge at a speed of 3000 rpm, wash it with deionized water 3 times to remove the hydrochloric acid, centrifuge again, take out the solid mixture at the bottom, dry and grind it at 60°C, and obtain a nano calcium-based montmorillonite with a positive charge on the outer layer, that is, an active proton particle group;

[0074] Add 50 parts of glycerol and 20 parts of chlorinated paraffin into a reaction kettle, stir evenly, then add 10 parts of thiosalicylic acid and 10 parts of potassium carbonate, and heat to 60°C for reaction for 8 hours under nitrogen protection; after the reaction is completed, extract with ethanol and vacuum dry at 100°C for 2 hours; pour the obtained light yellow liquid into tetrahydrofuran, adjust the pH value to 4 with hydrochloric acid, then pour into ethanol for extraction, vacuum dry at 80°C for 2 hours to obtain a light yellow liquid; add 200 parts of chloroform, 20 parts of long-chain fatty acid ester and 0.05 parts of N,N-dimethylformamide to 20 parts of the light yellow liquid, stir and react at 70°C for 5 hours, extract with ethanol, vacuum dry at 80°C for 2 hours to obtain a yellow liquid of long-chain fatty acid ester grafted with chlorinated paraffin;

[0075] Add 4.5 parts of active proton particles into 40 parts of yellow liquid, stir at high speed to disperse evenly, and obtain the main stabilizer.

[0076] Finally, the preparation method of the chlorinated polyvinyl chloride modified material is specifically as follows:

[0077] First, pour 110 parts of network cross-linked block chlorinated polyvinyl chloride into a high-speed mixer and mix at a speed of 1000r / min until the temperature reaches 85°C, then pour 7 parts of the main heat stabilizer into the high-speed mixer and continue mixing until the temperature reaches 91°C, then pour 1 part of octyltin mercaptan, 2 parts of oxidized polyethylene wax and 2 parts of ethylenebisstearamide, 0.5 parts of diisooctyldiphenylamine, and 1.5 parts of colorant into the high-speed mixer and continue mixing until the temperature reaches 120°C, discharge the material, and send the mixture into a cooling agitator to cool to 35°C to obtain a chlorinated polyvinyl chloride modified material.

[0078] Comparative Example 1: Chlorinated polyvinyl chloride is obtained by directly reacting polyvinyl chloride with chlorine gas, without chemically grafting dodecenyl succinic anhydride and block polymerized isooctyl acrylate, and the rest is the same as in Example 1; Comparative Example 2: Chlorinated polyvinyl chloride is obtained by directly reacting polyvinyl chloride with chlorine gas, without chemically grafting dodecenyl succinic anhydride and block polymerized isooctyl acrylate, and without the network cross-linked block chlorinated polyvinyl chloride obtained by physically blending with poly-α-methylstyrene and acrylonitrile fiber, and is directly replaced by chlorinated polyethylene in an equal amount, and the rest is the same as in Example 1;

[0079] Comparative Example 3: Directly use an equal amount of rare earth stabilizer to replace the long-chain fatty acid ester grafted chlorinated paraffin containing active proton particles as the main stabilizer, and the rest is the same as Example 1;

[0080] Comparative Example 4: Chlorinated polyvinyl chloride is directly obtained by reacting polyvinyl chloride with chlorine gas, without chemical grafting of dodecenyl succinic anhydride and block polymerized isooctyl acrylate, and without network cross-linked block chlorinated polyvinyl chloride obtained by physical blending with poly-α-methylstyrene and acrylonitrile fiber. Chlorinated polyethylene is directly used as an equal amount to replace the long-chain fatty acid ester grafted chlorinated paraffin containing active proton particles as the main stabilizer, and the rest is the same as in Example 1;

[0081] Comparative Example 5: The product involved in Example 1 of a method for improving the processing performance of chlorinated polyvinyl chloride resin with publication number CN113683851B.

[0082] Performance test of chlorinated polyvinyl chloride modified materials

[0083] 1. Thermal stability test

[0084] Dynamic thermal stability test: The test was conducted using a Haake rheometer, with the mixer temperature set at 180-210°C, the rotor speed at 30 rpm, the feed amount at 55 g, the mixed material weighed and added to the mixer, the rheometer started, and the test was terminated after 5 minutes when the torque was constant. The Vicat softening point was determined according to the B50 method specified in GB / T 8802-2001.

[0085] The chlorinated polyvinyl chloride modified materials obtained in Examples 1-3 and Comparative Examples 1-5 were subjected to a thermal stability test. The results of the 200°C stability time are shown in Table 1. A bar graph of the thermal stability time at 190°C, 195°C, 200°C and 205°C was made for Example 1, Comparative Example 1 and Comparative Example 4. Figure 1 ,from Figure 1It can be seen that when isooctyl acrylate is blocked and grafted with dodecenyl succinic anhydride in a water suspension polymerization reaction, and the main stabilizer of long-chain fatty acid ester grafted with chlorinated paraffin is coordinated with active proton particles, its heat resistance can be improved. The chlorinated polyvinyl chloride material with a chlorine content of 66% is finally obtained, and the product begins to decompose at about 120 minutes at 200°C. Comparative Example 1, which does not block isooctyl acrylate and grafted with dodecenyl succinic anhydride, begins to decompose at 200°C in 35 minutes. Comparative Example 3, which does not add the main stabilizer of long-chain fatty acid ester grafted with chlorinated paraffin containing active proton particles, can withstand a processing temperature of 200°C for 52 minutes, while Comparative Example 4, which does not add either, can only withstand a processing temperature of 200°C for 18 minutes before it begins to decompose. The comparison of the stability time of the embodiment and the comparative example at 190°C is not very obvious, but after 200°C, the stability time has changed significantly. This is because the strong polar groups (anhydride groups) introduced into the macromolecular chain increase the polarity and rigidity of the molecular chain, enhance the interaction force of the molecular chain, and because the double bond structure and partial chlorine structure in the molecular chain are reduced, and the long-chain fatty acid ester grafted chlorinated paraffin containing active proton particles completely inhibits the dechlorination reaction of the double bonds and partial chlorine structures on the molecular chain during the polymer thermoforming process, thereby inhibiting the self-catalytic degradation reaction of chlorinated polyvinyl chloride during high-temperature processing, and significantly improving the heat resistance and high-temperature stability of the chlorinated polyvinyl chloride modified materials of Examples 1-3.

[0086] As can be seen from Table 1, when the chlorine content is not much different, Examples 1-3 not only improve the Vicat softening point, but also significantly improve the stability time at high temperature. The chemical grafting and physical blending, as well as the main stabilizer of the long-chain fatty acid ester grafted with chlorinated paraffin containing active proton particles, are organically combined to effectively improve the heat resistance of the chlorinated polyvinyl chloride modified material, and expand the melting temperature and thermal decomposition temperature range. Therefore, the adjustable range of the processing temperature of the chlorinated polyvinyl chloride modified material is widened, and the processing fluidity is improved. The stability time at 200°C can reach about 120 minutes, which greatly reduces the difficulty of plasticizing chlorinated polyvinyl chloride.

[0087] The increase in Vicat softening point is because the presence of anhydride groups makes the polarity and rigidity of the macromolecular chain greater than that of chlorinated polyvinyl chloride, and the energy required for the movement of molecular chain segments is greater; during the processing, the molecular chains of chlorinated polyvinyl chloride chemically grafted with dodecenyl succinic anhydride and block polymerized isooctyl acrylate are less decomposed than chlorinated polyvinyl chloride. Therefore, according to the blending theory, its Vicat softening point is higher than that of chlorinated polyvinyl chloride. The increase in Vicat softening point means that the material has a stronger ability to maintain its shape and performance in a high temperature environment, which also helps to improve the processing performance of the material, especially when it needs to withstand high temperature or high mechanical load, materials with high Vicat softening point are more suitable.

[0088] Table 1 Thermal stability test results of chlorinated polyvinyl chloride modified materials

[0089] project Vicat softening point / ℃ 200℃ Stable time (min) Chlorine content (%) Example 1 126.1 122 66.8 Example 2 123.5 120 66.0 Example 3 125.4 125 66.5 Comparative Example 1 116.1 35 66.3 Comparative Example 2 115.4 26 66.2 Comparative Example 3 124.2 52 66.5 Comparative Example 4 113.7 18 66.0 Comparative Example 5 115.8 79 67.1

[0090] 2. Mechanical properties test results

[0091] The cooled mixture is fed into a twin-screw extruder for melt extrusion. The plastic standard specimens of chlorinated polyvinyl chloride modified materials are obtained by die head hot cutting method, and their mechanical properties are tested, including elastic modulus and elongation at break test: the elastic modulus and elongation at break of chlorinated polyvinyl chloride modified materials are measured by a universal tensile machine in accordance with GB / T1040.1-2018 to characterize the plasticizing efficiency of the plasticizer, and the stretching rate is 10mm / min. The impact strength is tested in accordance with GB / T1043.1-2008.

[0092] Table 2 Mechanical properties test results of chlorinated polyvinyl chloride modified materials

[0093]

[0094] The impact strength of the products obtained in Examples 1-3 is significantly increased because of the grafting of dodecenyl succinic anhydride and block polymerized isooctyl acrylate, and the synergistic grafting of long-chain fatty acid esters containing active proton particles with chlorinated paraffin. This is because the active proton particles can be added to the chlorinated polyvinyl chloride material as an elastomer and dispersed in the continuous phase of the matrix in a uniform granular state, thereby forming a so-called network cross-linked structure with macroscopic homogeneous phase and microscopic phase separation. When there is an external force, the elastic particles will act as a stress concentrator, inducing a large number of silver streaks and shear bands in the matrix. The generation and development of silver streaks and shear bands requires a large amount of energy, thereby increasing the impact strength of the elastomer system of Examples 1-3, and the network cross-linked block chlorinated polyvinyl chloride obtained by physical blending with poly-α-methylstyrene and acrylonitrile fiber has a significantly increased elongation at break due to the cross-linking of styrene and acrylonitrile fibers. When the impact strength increases significantly, the fiber will fill in the places where a large number of silver streaks and shear bands are generated, and continue to repair, so that the elongation at break is significantly improved, but because of the significant increase in impact strength, the bending strength will be slightly reduced. Therefore, compared with comparative examples 1-5, the elongation at break and impact strength of Examples 1-3 are significantly improved, which also makes the molecular structure of the material more superior, and its strength, thermal stability and heat resistance are greatly improved; the inherent defect of poor impact resistance of chlorinated polyvinyl chloride is improved, so that the plasticity is also significantly improved, and its scope of use is expanded, and it is particularly suitable for the preparation of heat-resistant and impact-resistant polymer material products.

[0095] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.

Claims

1. A method for preparing a chlorinated polyvinyl chloride modified material, characterized in that: The chlorinated polyvinyl chloride modified material is prepared from the following raw materials in parts by weight: 100-120 parts of chlorinated polyvinyl chloride with network cross-linked blocks; 5-8 parts of main stabilizer; 1-2 parts of auxiliary stabilizer; 2.0-4.0 parts of composite lubricant; 0.3-0.5 parts of antioxidant; 1.5-2.5 parts of colorant; The network cross-linked block chlorinated polyvinyl chloride is prepared by cross-linking modified chlorinated polyvinyl chloride and acrylonitrile fiber and poly-α-methylstyrene; the modified chlorinated polyvinyl chloride is prepared by chlorinating polyvinyl chloride, blocking isooctyl acrylate and grafting dodecenyl succinic anhydride; the main stabilizer is modified from chlorinated paraffin, long-chain fatty acid ester and nano-montmorillonite.

2. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 1, characterized in that: The modified chlorinated polyvinyl chloride, and its preparation method, are specifically: S001, in a reaction kettle, add polyvinyl chloride powder, talcum powder and deionized water, stir and mix to obtain a uniformly mixed suspension, introduce nitrogen to remove the air in the reaction kettle, use a vacuum pump to evacuate the gas in the reaction kettle to negative pressure, slowly raise the temperature to 85-88°C, then dropwise add initiator dibenzoyl peroxide, introduce chlorine, and react polyvinyl chloride and chlorine under a certain pressure. After reacting for 150-200 minutes, add dodecenyl succinic anhydride and isooctyl acrylate, stir evenly, slowly raise the temperature to 90-95°C, introduce chlorine for the second time, and continue to react for 5-7 hours; obtain a crude product; S002, after the reaction is completed, stop heating, when the reaction temperature drops to room temperature, blow out the remaining chlorine with nitrogen to the alkali solution tank for absorption, take out the crude product, add a certain amount of dilute alkali solution, stir for 5 minutes, then rinse with distilled water, and measure the pH value of the washing liquid with pH test paper; when the washing liquid is neutral, filter it and pour tetrahydrofuran into it to completely dissolve it, then add methanol to fully precipitate it, and then filter it; obtain the graft copolymer of block polymerized isooctyl acrylate grafted with dodecenyl succinic anhydride on the side chain, modified chlorinated polyvinyl chloride, and finally place it in a vacuum drying oven and dry it at 60±2℃ to constant weight.

3. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 1, characterized in that: The method comprises the following steps: S101, adding modified chlorinated polyvinyl chloride, polyα-methylstyrene and acrylonitrile fiber into a reaction kettle, heating the reaction kettle to 130-180°C under nitrogen protection, stirring at a speed of 500 rpm, and uniformly dispersing polyα-methylstyrene and acrylonitrile fiber in the modified chlorinated polyvinyl chloride, and continuing the reaction for 60-80 minutes to obtain a network cross-linked block chlorinated polyvinyl chloride; wherein the mass ratio of acrylonitrile fiber, polyα-methylstyrene and modified chlorinated polyvinyl chloride is 2-4:8-15:

100.

4. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 1, characterized in that: The main stabilizer is modified from chlorinated paraffin, long-chain fatty acid ester and nano-montmorillonite, specifically: S201, selecting nano calcium-based montmorillonite with a diameter of 50 to 80 nm, adding the nano calcium-based montmorillonite to deionized water, adding dilute hydrochloric acid and stirring evenly, so that the nano calcium-based montmorillonite is fully dispersed in the dilute hydrochloric acid solution, heating to 60° C., adding a mixed solution of glycerol and octadecyl dimethyl tertiary amine, stirring well, reacting for 1 to 2 hours, and obtaining a suspension of nano calcium-based montmorillonite; S202, adjusting the pH value of the suspension of nano calcium-based montmorillonite to 3.2-3.5 with hydrochloric acid, adding glutamic acid, stirring thoroughly, reacting for 2 hours, taking out the reaction solution and centrifuging at a speed of 3000 rpm, washing with deionized water 2-3 times to remove the hydrochloric acid, centrifuging again, taking out the solid mixture at the bottom, drying and grinding at 60° C. to obtain nano calcium-based montmorillonite with a positive charge on the outer layer, recorded as active proton particles; glycerol and octadecyl dimethyl tertiary amine are mixed in a mass ratio of 1:1; the mass ratio of the octadecyl dimethyl tertiary amine to the nano calcium-based montmorillonite is 1:4; the mass ratio of glutamic acid to the nano calcium-based montmorillonite is 1:1; S203, add glycerol and chlorinated paraffin into a reaction kettle, stir evenly, add thiosalicylic acid and potassium carbonate, and heat to 50-60° C. for reaction for 5-8 hours under nitrogen protection; after the reaction is completed, extract with ethanol, and vacuum dry at 100° C. for 2 hours; pour the obtained light yellow liquid into tetrahydrofuran, adjust the pH value to 4 with hydrochloric acid, and then pour into ethanol for extraction, and vacuum dry at 80° C. for 2 hours to obtain a light yellow liquid; the mass ratio of thiosalicylic acid, potassium carbonate and chlorinated paraffin is 1:1:2; S204, adding chloroform, long-chain fatty acid ester and N,N-dimethylformamide to the light yellow liquid, stirring and reacting at 60-70° C. for 4-6 hours, extracting with ethanol, and vacuum drying at 80° C. for 2 hours to obtain a yellow liquid in which the long-chain fatty acid ester is grafted onto the chlorinated paraffin; the mass ratio of the long-chain fatty acid ester to the chlorinated paraffin is 1:1; S205, adding active proton particles into the yellow liquid, stirring at high speed to disperse evenly, to obtain a main stabilizer, the mass ratio of active proton particles to long-chain fatty acid ester grafted chlorinated paraffin is 1:8-10.

5. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 1, characterized in that: The auxiliary stabilizer is an organic tin stabilizer, which is any one of methyl tin mercaptan and octyl tin mercaptan; The composite lubricant is a mixture of oxidized polyethylene wax and ethylene bisstearamide in a mass ratio of 1:1 to 2; The antioxidant includes at least one of p-diisooctyldiphenylamine and 2,6-tert-butyl-4-methylphenol; and the colorant is titanium dioxide.

6. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 2, characterized in that: The heating rate is controlled at 0.07-0.12°C / min, the temperature is raised to 85-88°C, chlorine is started to be passed, the chlorine passing rate is 1.8-2.1kg / min, and the pressure in the kettle is controlled to be 0.5-0.6MPa; the second chlorine passing chlorination is carried out at a chlorine passing rate of 3.8-4.2kg / min, the heating rate is controlled at 0.07-0.12°C / min, the temperature is raised to 90-95°C, and the pressure in the kettle is controlled to be 0.6-1.0Mpa; wherein, 100-120 parts of polyvinyl chloride powder, 2-4 parts of talc, 1-2 parts of dibenzoyl peroxide, and 150-250 parts of deionized water; the mass ratio of dodecenyl succinic anhydride, isooctyl acrylate and polyvinyl chloride powder is 6-8:20-30:100-120.

7. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 1, characterized in that: The preparation method of chlorinated polyvinyl chloride modified material is specifically as follows: S301, weighing network cross-linked block chlorinated polyvinyl chloride, a primary stabilizer, an auxiliary stabilizer, a composite lubricant, an antioxidant and a colorant according to a formula for use; S302, first pour the network cross-linked block chlorinated polyvinyl chloride into a high-speed mixer, mix at a speed of 800-1000r / min until the temperature reaches 75°C-85°C, then pour the main heat stabilizer into the high-speed mixer and continue to mix until the temperature reaches 88°C-92°C, then pour the auxiliary stabilizer, composite lubricant, antioxidant, and colorant into the high-speed mixer and continue to mix until the temperature reaches 110°C-130°C, discharge the material, and send the mixed material into a cooling agitator to cool it to 30°C-40°C, so as to obtain the chlorinated polyvinyl chloride modified material.

8. The method for preparing the chlorinated polyvinyl chloride modified material according to claim 1, characterized in that: The chlorinated polyvinyl chloride modified material is suitable for preparing heat-resistant and impact-resistant polymer material products.

Citation Information

Patent Citations

  • A method for improving the processing properties of chlorinated polyvinyl chloride resin

    CN113683851B

  • A chlorinated polyvinyl chloride composition, its preparation method and application

    CN115584096B